Penerapan Model Pembelajaran Snowball Throwing Berbantuan Media Ahaslides untuk Meningkatkan Hasil Belajar Siswa pada Materi Desain Grafis Kelas 10 di Smk Negeri 1 Japara - Anugrah, Aldi; Lutfi, Ahmad Fajri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve student learning outcomes in Graphic Design subjects through the implementation of the Snowball Throwing learning model assisted by AhaSlides media in Grade X of SMK Negeri 1 Japara in the academic year 2024/2025. The research employed a quantitative approach using a pre-experimental design with the one group pretest-posttest design. The population of this study consisted of 70 students from Grade X of the Visual Communication Design program at SMK Negeri 1 Japara. The sample was determined through purposive sampling, selecting 35 students from class X DKV 1. Data collection techniques included observation and tests, which were administered as pretests and posttests. Data were analyzed using descriptive statistics and inferential tests with the assistance of SPSS version 26. The findings revealed a significant improvement in students’ learning outcomes after applying the Snowball Throwing model assisted by AhaSlides. The mean pretest score of 51.11 increased to 79.43 in the posttest. The paired sample t-test results confirmed a significant difference between the pretest and posttest scores at the 0.05 significance level. Thus, it can be concluded that the implementation of the Snowball Throwing model assisted by AhaSlides is effective in enhancing student learning outcomes in Graphic Design at SMK Negeri 1 Japara.